An RCS based planar parallel v-shaped multi-resonators for wearable chipless RFID application - Sanaullah; Hossain, A K M Zakir; Hassim, Nurulhalim; Abbasi, Muhammad Inam (2024)
This paper introduces a new 8-bit planar parallel V-shaped multi-resonator (PVMR) specifically designed for RCS-based chipless RFID (CRFID) applications, focusing on its integration into fabric-based CRFID systems. The PVMR operates within the ultra-wideband (UWB) frequency spectrum. Simulations were conducted using both PCB-type substrates, including Rogers 3003 and flexible Kapton, as well as different fabric-based substrates: fleece, silk, felt, denim and pile. The results indicate a notable spectral density of up to 6.89bits/GHz using the Rogers 3003 substrate within a bandwidth of 1.16 GHz. Additionally, bending analysis was performed to evaluate the design’s compatibility with fabrics, and tests at various orientation angles along the z -axis were conducted to determine its suitability for applications like item tagging in supermarkets. These findings demonstrate the effectiveness of the proposed PVMR design and encourage CRFID designers to pursue the development of compact, high-capacity tags within the UWB range.